2014
DOI: 10.1111/jpc.12515
|View full text |Cite
|
Sign up to set email alerts
|

Does ondansetron have an effect on intramuscular ketamine‐associated vomiting in children? A prospective, randomised, open, controlled study

Abstract: A relatively high rate of KAV (29.7%) was observed, and the time to resumption of a normal diet after ketamine sedation was rather long. It turned out that, however, the adjunctive administration of ondansetron did not effectively reduce the incidence of KAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…This is in agreement with previous studies that concluded that the rate of emesis reached a maximum level at the age of 12 years. (12,21,22) While we concur that patient age plays an important role in the rate of adverse events, our analysis showed that all children aged ≥ 8 years were at a higher risk of vomiting following IM ketamine sedation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This is in agreement with previous studies that concluded that the rate of emesis reached a maximum level at the age of 12 years. (12,21,22) While we concur that patient age plays an important role in the rate of adverse events, our analysis showed that all children aged ≥ 8 years were at a higher risk of vomiting following IM ketamine sedation.…”
Section: Discussionmentioning
confidence: 63%
“…(17) However, its use in preventing emesis following ketamine sedation has seen mixed views. (17,21) For instance, a prospective study in 2014 showed no improvement in the rate of emesis with the administration of prophylactic oral ondansetron for IM ketamine sedation. (21) However, the mean age of the children who participated in the study was 30 months, which is much lower than the age range of the at-risk adolescent population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prospective randomised controlled studies showed no significant difference between intramuscular ketamine alone or ketamine with antiemetic, although both studies have significant limitations. Lee  et al 3 in 2014 had a statistically significantly higher mean age of children in the ketamine with ondansetron group than in the ketamine alone group, while Lee  et al 4 in 2012 only included children younger than 5 years.…”
Section: Commentsmentioning
confidence: 99%
“…2225 Olguların %0.3'ünde sadece midazolam uyguladığımızı, olguların %70.6'sında ise ketaminmidazolam kombinasyonunu tercih ettiğimiz belirledik. Bu sayede ek doz ketamin gereksinimi azalttığımızı, midazolamın amnezi özelliğinden yararlandığımızı, %3 oranında epilepsi saptadığımız olgularda ketaminin epilepsi eşiğini düşüren etkisini antagonize ederek 26 midazolamın antikonvülzan özelliğinden yararlandığı-mızı sunmak istedik. Bu sayede epileptik olgularda ketamin uygulamasına sekonder nöbet ya da benzeri yan etkilerle karşılaşmadık.…”
unclassified